The Effect of Current Ratio and Earning Per Share on Stock Prices in Manufacturing Companies in the Agricultural Sector - Baharuddin, Baharuddin; Wahab, Abdul; Sultan, Zulkifli (Terbuka Journal of Economics and Business, 2022)
This study aims to determine the effect of (1) the effect current ratio on stock prices (2) the effect of earning per share on stock prices (3) the effect current ratio and earning per share on stock prices both partially and simultaneously on stock prices in agricultural sector manufacturing companies listed on the Indonesia stock Exchange. The research method used is multiple linear regression analysis method correlation coefficient (R), The coefficient of determination (R2), f test and t test data types used are secondary data with a total sample size of 4 companies. The results of this study were obtained with a correlations value of (R) of 0,581 so there is a very strong relationship between the variable stock price and the variabel current ratio. The coefficient of determination (R2) is 0,338. Which means that 0f the variable stock price can be explained by the variable current ratio and earnings per share remaining can be explained by other variables not not axamined. In test f the f-count is and f table value of (4,334 > 3,59) with a significant value of (0,014 < 0,05) the current ratio and earning per share together have a significant effect on stock prices. X1 t-count 2,752 > t-table 2,109 means that current ratio has and effect but not significant on stock prices and the X2 t-test is 1,294 < 2,109 means that earning per share has but not effect but is not significant on stock in agricultural sector manufacturing companies listed on the IDX, one and two rejected while the fifth hypothesis is accepted